Drip fertilization improve water and nitrogen use efficiency by optimizing root and shoot traits of winter wheat - Ma, Shoutian; Meng, Ye; Han, Qisheng; Ma, Shouchen (Frontiers in Plant Science, 2023)
Proper irrigation and fertilization measures can not only improve water and fertilizer utilization efficiency, but also have important significance in ensuring agricultural environment security and sustainable development. A field experiment was conducted to determine the optimal drip fertilization measure of winter wheat and explain its mechanism by analyzing the physiological and ecological characteristics and utilization efficiency of water and nitrogen under different irrigation and fertilization methods. The plants were treated with three irrigation and fertilization methods: the traditional irrigation and fertilization method (CK), surface drip fertilization (I1) and underground drip fertilization (I2). The results demonstrated that different irrigation methods had various effects on population and physiological characteristics of wheat. The plant height, leaf area and tiller number of I1 were significantly higher than those of CK during the whole growth period. I2 decreased plant height, leaf area and tiller number at jointing stage, but at flowering stage, the leaf area of I2 t was significantly higher than that of CK. Different irrigation methods also affected the root distribution of wheat. At flowering stage, I1 had lower root biomass than CK in all soil layers. The upper root system of I2 was smaller, but the deep root system was larger compared with the control. I1 and I2 had lower total root weight and higher shoot biomass compared to CK, so their root-shoot ratio decreased significantly. I1 and I2 increased and instantaneous water use efficiency (IWUE) by increasing the photosynthetic rate (Pn) and reducing transpiration rate (Tr) at the flowering stage, while I2 had a similar Pn to I1, but reduced Tr, resulting in a higher IWUE than I1. Both I1 and I2 also increased root efficiency, root activity, and Fv/Fm of wheat at the late growth stage, promoting accumulated dry matter after flowering (ADM) and pre-flowering dry matter remobilization (DMR), leading to a significant increase in grain yield. In addition, I1 and I2 had significantly higher water productivity (WP), irrigation water productivity (IWP), nitrogen partial productivity (NPP) and nitrogen agronomic efficiency (NAE) than CK, especially I2 had the highest IWP, WP, NPP and NAE.